Fractionation of stable nitrogen isotopes (15N/14N) during enzymatic deamination of glutamic acid: Implications for mass and energy transfers in the biosphere - Goto, Akiko S.; Miura, Kasumi; Korenaga, Takashi; Hasegawa, Takashi; Ohkouchi, Naohiko; Chikaraishi, Yoshito (GEOCHEMICAL JOURNAL, 2018)
Isotopic fractionation of nitrogen associated with the trophic transfer of amino acids in food webs has recently been used as a powerful tool to estimate the accurate trophic levels of heterotrophic organisms. During the grazing process (i.e., trophic transfer), the amino acid, glutamic acid, is significantly enriched in 15N (by ~6–9‰) from diets to consumer heterotrophs; this is most likely caused by isotopic fractionation with the preferential deamination of 14N-amino group in glutamic acid during its metabolism. However, few studies determined the isotopic fractionation factor (α) of this process, which limits our understanding of the mechanism responsible for the isotopic fractionation and thus restricts its applicability in assessing the mass and energy transfers with respect to the amino acid assimilation/dissimilation cycle in the biosphere. In this study, we evaluate the α value associated with the enzymatic deamination of glutamic acid in vitro. Glutamic acid is gradually enriched in 15N by up to 4.0‰, when the deamination flux is increased up to 45.4%. The α value calculated is 0.9938 ± 0.0005 if the Rayleigh fractionation model is applied to the enrichment in 15N. Thus, we demonstrate the relationship between isotopic fractionation and deamination flux: for example, 8.0‰ fractionation corresponds to that 72 ± 3% of the diet-derived glutamic acid is deaminated in the consumer species at each shift of trophic levels in a food web.